The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.resp.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow during acute hypoxia in individuals susceptible to acute mountain sickness

Abstract: Individuals susceptible to high altitude pulmonary edema show altered pulmonary vascular responses within minutes of exposure to hypoxia. We hypothesized that a similar acute-phase vulnerability to hypoxia may exist in the brain of individuals susceptible to acute mountain sickness (AMS). In established AMS and high-altitude cerebral edema, there is a propensity for vasogenic white matter edema. We therefore hypothesized that increased cerebral blood flow (CBF) during acute hypoxia would also be disproportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
(41 reference statements)
4
30
0
Order By: Relevance
“…They found a greater degree of rCBF in the forebrain grey matter during acute hypoxia and speculated that this localised response might be ascribed to an acute compensatory mechanism involving regions with increased sensitivity to oxygen deficits, possibly because they would develop reversible neuronal impairment. However, DYER et al [30] found that there was no difference in the percentage change of rCBF in different regions of the brain during acute hypoxia. The discrepant findings might have been due to differences in the degree of hypoxia or differences in the methods used to assess rCBF (fMRI versus single-photon emission computed tomography).…”
Section: Discussionmentioning
confidence: 96%
“…They found a greater degree of rCBF in the forebrain grey matter during acute hypoxia and speculated that this localised response might be ascribed to an acute compensatory mechanism involving regions with increased sensitivity to oxygen deficits, possibly because they would develop reversible neuronal impairment. However, DYER et al [30] found that there was no difference in the percentage change of rCBF in different regions of the brain during acute hypoxia. The discrepant findings might have been due to differences in the degree of hypoxia or differences in the methods used to assess rCBF (fMRI versus single-photon emission computed tomography).…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, an expansion of the extracellular space occurs (vasogenic edema), which is only observed with more prolonged or severe hypoxic exposure in conjunction with high-altitude cerebral edema. In opposition to this hypothesis, Hunt et al 8 identified no evidence linking cerebral edema to acute mountain sickness susceptibility after 2 days at 3,800 m, although this result is not surprising given the low incidence of high-altitude cerebral edema at altitudes between 2,500 and 5,000 m. 22 Given that a central tenant of the intracellular swelling explanation is disruption of cellular membrane Na þ /K þ ATPase, it should be remembered that global increases in cerebral blood flow 23,24 and maintained or increased global cerebral metabolic rate of oxygen 11,25,26 have been observed. Thus, it is possible that the reduction in white matter water mobility as observed herein is the consequence of regionally reduced white matter blood flow and oxygen delivery because of transient or persistent elevations in intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The first step down the path to brain swelling is hypothesized to be increased cerebral blood flow and associated increased cerebral blood volume, which directly produces brain swelling-leading to increased capillary pressure and cerebral edema. We previously found that increased cerebral blood flow is a common outcome of ascent to high altitude, 17 as is cerebral swelling and reduced CSF volume, 18 but neither was associated with a greater propensity to develop AMS. An alternate hypothesis for brain swelling and symptoms of AMS may relate to compromised cerebral energy status.…”
Section: Diffusion-weighted Mri Changes In Acute Mountain Sickness Jsmentioning
confidence: 99%